Growth mechanism of primary Ti5Si3 phases in special brasses and their effect on wear resistance. (20th January 2021) - Wang, Xianlong; Jie, Jinchuan; Liu, Shichao; Dong, Zhuangzhuang; Yin, Guomao; Li, Tingju
Highlights: Ti5 Si3 phase exhibits a hexagonal prism morphology along <0001> bounded by {100} faces. The morphology of primary Ti5 Si3 phase changes with the increasing content of Ti5 Si3 in brass. The wear mechanism of brass depends on the volume fraction and morphology of the Ti5 Si3 phase. The formation of hollow in Ti5 Si3 is considered to be the reason for the abnormal increase in friction coefficient. Abstract: In the present work, in-situ Ti5 Si3 reinforced special brasses were prepared by melt reaction method. The synthesized Ti5 Si3 phase shows various morphologies in brasses with different Ti5 Si3 content, and the 3D morphological evolution of primary Ti5 Si3 and its growth mechanism were investigated. The Ti5 Si3 crystal, which bears D88 hexagonal crystal structure, grows along <0001> direction and is revealed by {101̅0} faces during growth. With the increase of Ti5 Si3 content in the brasses, the morphology of primary Ti5 Si3 significantly changes from fibers to hexagonal prisms to short-rods with hollow. In addition, the influence of Ti5 Si3 volume fraction and morphology on the wear behavior of special brass was also revealed. It was substantiated that the wear resistance increases with the increasing volume fraction of Ti5 Si3, and the corresponding wear mechanism changes from delamination to slight adhesive wear and abrasive wear. However, the friction coefficient shows an abnormal increase when most of the Ti5 Si3 containing hollows appears in the brass. That is mainly due to the fact that the Ti5 Si3 is easier to break and fall off resulted by the hollow as a crack source, which makes it unable to resist the plastic deformation of the contact surface during the sliding.